The Practice of ‘Urethral Sounding’ Complicated by Retained Magnetic Beads Within the Bladder and Urethra: Diagnosis and Review of Management - Lindsay, Jamie Stephen (Am J Case Rep, 2019)
Patient: Male, 18-year-old Final Diagnosis: Foreign body in urethra and bladder Symptoms: Dysuria Medication: — Clinical Procedure: — Specialty: Urology OBJECTIVE: Rare disease BACKGROUND: The emergency treatment of a retained foreign body within the urethra and bladder is an uncommon clinical scenario within adult urology. Beyond the medical field, the placement of an object/s into the urethra is known as ‘urethral sounding’ and encompasses a sexual practice performed to heighten arousal and pleasure. The medical literature highlights the morbidity associated with this practice, most commonly when the sounding device can no longer be retrieved by the participant. CASE REPORT: A case report involving an 18-year-old male requiring endoscopic retrieval of 60 magnetic metal beads intended for the purpose of urethral sounding. The management was uncomplicated and the patient suffered no long-term complications at follow-up. A brief review of the literature reveals 9 reports since 2013 of magnetic beads retained within the bladder following this autoerotic practice in adults. CONCLUSIONS: The insertion of multiple small magnetic beads into the urethra is an inadvisable method for use in the practice of urethral sounding due to the lack of non-operative management options. This is due to the high risk of the magnetic beads forming a magnetized cluster once the chain enters the bladder. All cases assessed report successful management with both minimally invasive and open approaches.